ESTUDO DA CONJUGAÇÃO DE NANOPARTÍCULAS DE OURO (AUNP) COM FLUORÓFOROS ORGÂNICOS DERIVADOS DO BORODIPIRROMETENO (BODIPY) - Silveira, Clarice Emilia da (2021)
The interaction between fluorescent molecules and metallic nanoparticles has aroused great interest due to its potential applications in metal ion detection, intracellular thiol sensor, insecticide detection, fluorescence immunoassays, measurement of the distance between binding contacts and pH measurements intracellular. The presence of AuNPs can alter the photophysical properties of fluorescent compounds, increasing, decreasing and/or shifting the fluorescence emission. The objective of this work is to unravel an interaction between AuNPs and fluorophores derived from borodipyrromethenes (BODIPYs). For this purpose, nine fluorophores and different conjugation objectives were used, through electrostatic and covalent bonding and with the use of a spacer. The data seem to indicate that AuNPs behave like quenchers, that is, they are capable of suppressing the fluorescence of the studied compounds. In this study, we developed a method for the functionalization of AuNPs with BODIPYs, as we believe in the application of the material in nano and biosensors, nanotoxicology, and in fluorescent immunochromatographic techniques based on the junction of optical and electronic properties of AuNPs and fluorescent compounds.